Between tropical forests and black communities. The 19th century travelers facing the otherness of the Colombian Pacific - Peralta Agudelo, Jaime Andrés (2022)
This article will analyze the perception schemes and discursive platforms through which nineteenth-century foreign travelers presented in their countries of origin and to the national elites the natural environment and the sociocultural universe of the black communities that inhabited the Pacific coast of the young Republic of Colombia. It will be seen that the tropical rainforest was perceived as an inexhaustible storehouse of commodities or as a strategic axis of world trade. At the same time, the cultural legacy and the historical trajectory of the Afro-Pacific groups were disqualified, and they were taken as the greatest obstacle to the «progress» of this area, but also as a cheap workforce to serve the capitalist system that emerged after the decline of the Spanish Empire.